MOBILE CECUM IN THE ETIOPATHOGENESIS OF IRRITABLE BOWEL SYNDROME: EVIDENCE, IMPACTS AND DIAGNOSTIC PERSPECTIVES (REMUNOM, 2025)
Introduction: Mobile cecum is understood as the anatomical anomaly, of embryological origin, that affects segments of the large intestine; which may generate symptoms in acute or chronic conditions. This condition tends to affect 10 to 20% of the population, with a predominance in females; with distension, abdominal pain, cramps, constipation, and diarrhea being the most common manifestations in symptomatic cases. Meanwhile, Irritable Bowel Syndrome (IBS) is a chronic condition, for which the exact pathophysiological mechanisms are still unknown; but it affects women twice as often as men and tends to cause recurrent chronic abdominal pain and changes in bowel habits. Objective: To investigate how knowledge of a possible etiological relationship between Mobile Cecum and the development of Irritable Bowel Syndrome could assist in the differential diagnosis, treatment, and prognosis of these syndromes. Method: This is an integrative review carried out through a bibliographic search, using the following databases: PubMed, Google Scholar, and Scopus. Additionally, the artificial intelligence tool SciSpace was used to search for two recent articles. Results: Of the 15 articles addressed in this review, there were studies that discussed radiographic diagnostic techniques, effective treatment such as cecopexy, as well as epidemiological approaches and clinical implications of the syndromes. Conclusion: Based on the data gathered from this bibliography, Mobile Cecum is suggested to be a significant anatomical marker that is commonly present in cases of Irritable Bowel Syndrome. Thus, investigating the existence of this anatomical variation in individuals with IBS, through the use of imaging exams, would be beneficial.